Clostridium difficile toxin testing by National Health Service (NHS) acute Trusts in England: 2008–2013. (September 2015) - Gerver, S.M.; Johnson, A.P.; Hope, R.J.
Abstract: In October 2007, a governmental 3-year target to reduce Clostridium difficile infection (CDI) by 30%, with financial penalties levied for failure, was introduced in England. This target was met within just 1 year, leading to speculation of 'gaming', with hospitals empirically treating possible CDI in the absence of a microbiological diagnosis, to avoid having to report confirmed cases. An analysis of aggregate mandatory data on levels of testing for C. difficile toxin showed little evidence of a fall in testing during the steepest infection rate reductions, suggesting that this was not a major factor in the decline in CDI.